2022
DOI: 10.15585/mmwr.mm7150a4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of SARS-CoV-2 and Influenza Coinfection and Clinical Characteristics Among Children and Adolescents Aged <18 Years Who Were Hospitalized or Died with Influenza — United States, 2021–22 Influenza Season

Abstract: The 2022-23 influenza season shows an early rise in pediatric influenza-associated hospitalizations (1). SARS-CoV-2 viruses also continue to circulate (2). The current influenza season is the first with substantial co-circulation of influenza viruses and SARS-CoV-2 (3). Although both seasonal influenza viruses and SARS-CoV-2 can contribute to substantial pediatric morbidity (3-5), whether coinfection increases disease severity compared with that associated with infection with one virus alone is unknown. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 5 publications
4
18
0
2
Order By: Relevance
“…This report, as the sole cross‐sectional influenza surveillance conducted in Tokyo, has revealed a distinct period of influenza absence, followed by its resurgence. The study provides evidence that the decrease in the number of influenza tests did not necessarily lead to a decrease in the number of positive cases 9 and supports the notion that simultaneous infection with influenza and SARS‐CoV‐2 is rare 24,26 …”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This report, as the sole cross‐sectional influenza surveillance conducted in Tokyo, has revealed a distinct period of influenza absence, followed by its resurgence. The study provides evidence that the decrease in the number of influenza tests did not necessarily lead to a decrease in the number of positive cases 9 and supports the notion that simultaneous infection with influenza and SARS‐CoV‐2 is rare 24,26 …”
Section: Discussionsupporting
confidence: 68%
“…The study provides evidence that the decrease in the number of influenza tests did not necessarily lead to a decrease in the number of positive cases 9 and supports the notion that simultaneous infection with influenza and SARS-CoV-2 is rare. 24,26 Additionally, this investigation presents initial evidence confirming a reduction in influenza cases among the elderly during the COVID-19 pandemic, as alluded to numerically in the database of the Tokyo Metropolitan Government. 13 We have concerns that a resurgence of influenza might occur after the relaxation of infection control measures such as universal mask wearing and the restoration of active international travel.…”
Section: Discussionsupporting
confidence: 55%
“…(32/575) of hospitalized pediatric influenza patients had SARS-CoV-2 coinfection, during the 2021-2022 influenza season. 37 In addition, the study identified increased use of mechanical ventilation among coinfected patients, indicating potentially more severe disease among coinfected patients. 37 Consistently, our study reports patients with coinfections suffered more severe symptoms than those with monoinfection.…”
Section: Discussionmentioning
confidence: 89%
“…Coinfection significantly increases the risk of severe outcomes such as respiratory distress, the need for invasive mechanical ventilation, and death. [66][67][68] Therefore, in the post-pandemic era, it is crucial to address how SARS-CoV-2 and seasonal respiratory virus coinfections impact the severity of childhood RTIs. Nowadays, as SARS-CoV-2 has become less virulent, COVID-19 may gradually evolve into a seasonal and regional epidemic requiring regular vaccinations.…”
Section: Reflections On the Diagnosis And Treatment Of Rtis In Childr...mentioning
confidence: 99%
“…In particular, IFV, HRSV, and HADV are the most commonly observed coinfecting viruses. Coinfection significantly increases the risk of severe outcomes such as respiratory distress, the need for invasive mechanical ventilation, and death 66–68 . Therefore, in the post‐pandemic era, it is crucial to address how SARS‐CoV‐2 and seasonal respiratory virus coinfections impact the severity of childhood RTIs.…”
Section: Reflections On the Diagnosis And Treatment Of Rtis In Childr...mentioning
confidence: 99%